Corporate Collaboration In Financing Schemes: Qualitative Analysis Of Risks And Benefits Of Financing To Group Companies With Shared Responsibility - Grace Yulianti; Mohammad Chaidir; Seger Santoso (International Journal of Business Law, Business Ethic, Business Comunication & Green Economics, 2024)
This study aims to analyze the risks and benefits of joint liability financing schemes for groups of companies through a qualitative literature review approach. This financing scheme offers solutions for companies facing capital constraints by enhancing access to credit through collective responsibility. The results of the review indicate that this scheme provides benefits such as increased financing opportunities, mitigation of default risks, and peer monitoring among group members. However, it also presents risks such as overinvestment and moral hazard, where company members may tend to make larger investments or neglect their obligations due to the protection of joint liability. Additionally, the effectiveness of the scheme heavily relies on the group structure, with smaller and more homogeneous groups having lower risks compared to larger and more heterogeneous ones. This study concludes that joint liability financing schemes can be an effective solution if these risks are well-managed through stringent oversight and fair financing policies.